Habitual abortion. Endocrine factor. - Coyotupa, Juan (2015)
The endrocrino factor to cause 3 or more consecutive spontaneous abortions leads us to progesterone deficiency, since alteration in thyroid function or diabetes can cause occasional abortion, but hardly habitual abortion. Inadequate function of the ovary after ovulation constitutes the luteal phase defect.